Nucleus accumbens volume is related to obesity measures in an age‐dependent fashion. (11th December 2019) - García‐García, Isabel; Morys, Filip; Dagher, Alain
Abstract: Motivation theories of obesity suggest that one of the brain mechanisms underlying pathological eating and weight gain is the dysregulation of dopaminergic circuits. Although these dysregulations likely occur at the microscopic level, studies on grey matter volume report macroscopic differences associated with obesity. One region suggested to play a key role in the pathophysiology of obesity is the nucleus accumbens (NAcc). We performed a meta‐analysis of findings regarding NAcc volume and overweight/obesity. We additionally examined whether grey matter volume in the NAcc and other mesolimbic areas depends on the longitudinal trajectory of obesity, using the UK Biobank dataset. To this end, we analysed the data using a latent growth model, which identifies whether a certain variable of interest (eg, NAcc volume) is related to another variable's (body mass index [BMI]) initial values or longitudinal trajectories. Our meta‐analysis showed that, overall, NAcc volume is positively related to BMI. However, further analyses revealed that the relationship between NAcc volume and BMI is dependent on age. For younger individuals, such a relationship is positive, whereas, for older adults, it is negative. This was corroborated by our analysis in the UK Biobank dataset, which includes older adults, where we found that a higher BMI was associated with a lower NAcc and thalamus volume. Overall, the present study suggests that increased NAcc volume at a young age might be a vulnerability factor for obesity, whereas, at an older age, decreased NAcc volume with increased BMI might be an effect of prolonged influences of neuroinflammation on the brain.